2023
DOI: 10.1109/tpwrd.2023.3234364
|View full text |Cite
|
Sign up to set email alerts
|

Wear of the Arcing Contacts and Gas Under Free Burning Arc in SF$_{6}$ Alternatives

Abstract: In gas insulated substations, the main trend is to move from SF6 to more environmentally friendly alternatives. The main SF6 alternatives are mixtures based on CO2, with additives of O2 and the fluorinated gases C4F7N or C5F10O. Mixtures with fluorinated additives of up to 10 % were investigated in a test setup with a free burning arc. Gas composition was measured for each gas after mixing, and in-between some arcing sequences. Gas mixtures were investigated by three mobile gas analyzers and by three laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For instance, C 2 F 6 possesses a GWP of 11,000, while CF 4 boasts an atmospheric lifetime of 50,000 years . The formation of these byproducts is affected by multiple factors, such as buffer gas composition, arc current, temperature, circuit breaker geometry, and others . Chen et al found that C 2 F 3 N began to form when heated to 500 °C for 72 h .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, C 2 F 6 possesses a GWP of 11,000, while CF 4 boasts an atmospheric lifetime of 50,000 years . The formation of these byproducts is affected by multiple factors, such as buffer gas composition, arc current, temperature, circuit breaker geometry, and others . Chen et al found that C 2 F 3 N began to form when heated to 500 °C for 72 h .…”
Section: Introductionmentioning
confidence: 99%
“… 7 The formation of these byproducts is affected by multiple factors, such as buffer gas composition, arc current, temperature, circuit breaker geometry, and others. 36 Chen et al found that C 2 F 3 N began to form when heated to 500 °C for 72 h. 37 Li et al discovered that C 4 F 7 N/N 2 mixtures that use O 2 as an additional buffer gas have an increased CF 4 concentration and a decreased C 2 F 6 concentration when discharged. 38 These parameters also affect the insulating ability of C 4 F 7 N. For example, as the distance between the arc contacts in a circuit breaker increases, the insulating efficiency of the gas is improved.…”
Section: Introductionmentioning
confidence: 99%